2022
DOI: 10.3390/ijerph19159158
|View full text |Cite
|
Sign up to set email alerts
|

Non-Specific Low Back Pain, Dietary Salt Intake, and Posterior Lumbar Subcutaneous Edema

Abstract: Low back pain is the world’s leading disability, but the etiology of the majority of low back pain is non-specific with no known cause. Moreover, overuse of opioids to treat low back pain is a widespread problem. This paper proposes that non-specific low back pain may be associated with excessive intake of dietary salt, potentially mediated by posterior lumbar subcutaneous edema. In addition to pain, symptoms of edema include swelling, tightness, and stiff joints, which are common complaints of people with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The authors determined cutoff values to predict low back pain and spine degeneration for females (subcutaneous fat thickness > 8.45 mm) and males (> 9.4 mm) 62 . Furthermore, diet—particularly dietary salt intake—may influence lumbar subcutaneous edema, which could in turn influence non-specific low back pain 63 . Clinical practitioners should factor in such changes in subcutaneous tissue thickness and composition when examining thoracolumbar soft tissue structures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors determined cutoff values to predict low back pain and spine degeneration for females (subcutaneous fat thickness > 8.45 mm) and males (> 9.4 mm) 62 . Furthermore, diet—particularly dietary salt intake—may influence lumbar subcutaneous edema, which could in turn influence non-specific low back pain 63 . Clinical practitioners should factor in such changes in subcutaneous tissue thickness and composition when examining thoracolumbar soft tissue structures.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine headaches in particular are often comorbid with MS [77], and evidence suggests that sodium chloride intake is associated with migraine headache pain [78]. Sodium chloride intake is also associated with posterior lumbar subcutaneous edema in nonspecific low back pain [79]. Coincidently, a recent study of the French MS population found that the prevalence of lower back pain is two to three times higher than in the general population [80].…”
Section: Migraine Non-specific Low Back Pain and Msmentioning
confidence: 99%
“…Low back pain (LBP) is a widespread global health problem, a cause of long-term health problems for people across different incomes levels and countries ( 1 , 2 ). According to the Global Burden of Disease Study of 2019 (GBD 2019), LBP was the leading cause of years lived with disability (YLDs) worldwide, accounting for about 7.4% (range: 6.2%–8.7%) of the total global YLDs.…”
Section: Introductionmentioning
confidence: 99%